2000
DOI: 10.1007/s004420051019
|View full text |Cite
|
Sign up to set email alerts
|

Is atmospheric CO 2 a selective agent on model C 3 annuals?

Abstract: Atmospheric CO partial pressure (pCO) was as low as 18 Pa during the Pleistocene and is projected to increase from 36 to 70 Pa CO before the end of the 21st century. High pCO often increases the growth and reproduction of C annuals, whereas low pCO decreases growth and may reduce or prevent reproduction. Previous predictions regarding the effects of high and low pCO on C plants have rarely considered the effects of evolution. Knowledge of the potential for evolution of C plants in response to CO is important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(169 citation statements)
references
References 22 publications
4
162
0
1
Order By: Relevance
“…This is despite substantial evidence indicating that subambient [CO 2 ] concentrations are an important selective agent [11,71] [63,65,69] or herbivory [85,86], evolutionary effects may be more likely in more stressful biotic environments. Similarly, evolutionary effects of elevated [CO 2 ] also may be more likely when plants experience abiotic stress, such as drought or nutrient limitation.…”
Section: Question 1: Have Plants Evolved In Response To Varying [Comentioning
confidence: 94%
See 1 more Smart Citation
“…This is despite substantial evidence indicating that subambient [CO 2 ] concentrations are an important selective agent [11,71] [63,65,69] or herbivory [85,86], evolutionary effects may be more likely in more stressful biotic environments. Similarly, evolutionary effects of elevated [CO 2 ] also may be more likely when plants experience abiotic stress, such as drought or nutrient limitation.…”
Section: Question 1: Have Plants Evolved In Response To Varying [Comentioning
confidence: 94%
“…The first approach uses 'selection in controlled environments' experiments (sensu [75] e.g. [68,71] 2 ]. The advantage of the selection in a controlled environment approach is that it specifically tests for whether an evolutionary response occurs; however, the mechanisms underlying the response cannot be identified.…”
Section: Question 1: Have Plants Evolved In Response To Varying [Comentioning
confidence: 99%
“…Experiments using reciprocal transplantation after selection at elevated CO 2 are the clearest way of demonstrating an evolutionary response [6], but few have been reported for elevated CO 2 [7][8][9][10][11]. Some reciprocal transplant experiments in plants have shown adaptation to CO 2 concentration below current levels, but they have consistently failed to detect specific adaptation to elevated CO 2 [8,9]. The only study of land plants that has shown an effect of high CO 2 across generations was a single-generation reciprocal transplant experiment that was not capable of distinguishing between maternal effects and genetic change [7].…”
Section: Introduction (A) the Response Of Primary Producers To Risingmentioning
confidence: 99%
“…This effect may result from interactions with ethylene, a C-based plant hormone that stimulates germination. Other studies have found that seeds from parental plants reared in elevated CO 2 may have higher C:N ratios and develop into smaller, slower-growing seedlings (Huxman et al 1998;Ward et al 2000). Reproductive impacts of increased N deposition are equivocal: plant fecundity may increase or remain unchanged as a result of increased N availability (Gordon et al 1999;Callahan et al 2008).…”
Section: Global Change Impacts On Forest Reproduction Recruitment Amentioning
confidence: 99%